Discrimination of cosmic-ray in scintillation region and light-guide for plastic scintillation detectors using 5GSPS readout system - Nguyen , Quoc Hung; Vo , Hong Hai; Masaharu , Nomachi; Nguyen , Trong Tin (Nuclear Science and Technology, 2015)
At sea level, the measurement of energy spectrum for cosmic-ray flux determination using two-coincidence plastic scintillation detectors with “traditional” electronic-readout system may include not only cosmic-ray in scintillator region but also light-guide region. In this work, we carry out a measurement of cosmic-ray using two-coincidence plastic scintillation detectors with size of each 80cm×40cm×3cm thick, and an electronic-readout system of 5GSPS (i.e. 200 ps sampling-time resolution). With the readout system, the shapes of pulses from scintillation detectors can be observed. The behavior of time responses of pulses in a plastic scintillator and a light-guide may be different. Based on some characteristics of these responses (such as pulse width, its falling edge, etc. ), it is possible to discriminate cosmic-ray in scintillation region from light-guide region. The vertical cosmic-ray flux was measured to 0.1×10-3count.s-1cm-2. The obtained results will be presented and discussed in detail. The experiment was set up and measured at the Nuclear laboratory, Department of Nuclear Physics, University of Science, HCMC-Vietnam National University